2022
DOI: 10.1002/jhbp.1285
|View full text |Cite
|
Sign up to set email alerts
|

The role and timing of endoscopic retrograde cholangiopancreatography in acute biliary pancreatitis without cholangitis: A nationwide analysis

Abstract: Background/Purpose The role and optimal timing of endoscopic retrograde cholangiopancreatography (ERCP) in acute biliary pancreatitis without cholangitis (ABPwoC) remains unclear. Using a large national database, we aimed to examine hospitalization outcomes of patients with ABPwoC as a function of the performance and timing of ERCP. Methods This was a retrospective study of adult patients with ABPwoC utilizing the National Inpatient Sample from 2016–2017. Patients who underwent inpatient ERCP were stratified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 88–92 RCTs in specific patient subpopulations showed that ERCP with endoscopic sphincterotomy performed early (within 24 h) was beneficial in biliary AP associated with cholangitis, 93 , 94 but it was not advantageous generally in any biliary cases. 95 Although a recent retrospective study challenged this concept by showing that early ERCP was associated with lower mortality rates in a large, nationwide analysis of patients with biliary AP without cholangitis, 96 the findings of a well-designed, multicenter RCT support the initiative that ERCP in AP is indicated only in patients with cholangitis or persistent cholestasis. 97 The contradictions regarding the use of ERCP in AP lead to adjustments of study protocols, which resulted in identification of specific subpopulation of patients (ie, those with cholangitis), who can benefit the most from the intervention if it is performed in a timely manner.…”
Section: Future Possibilities Of Precision Medicine In Apmentioning
confidence: 99%
See 1 more Smart Citation
“… 88–92 RCTs in specific patient subpopulations showed that ERCP with endoscopic sphincterotomy performed early (within 24 h) was beneficial in biliary AP associated with cholangitis, 93 , 94 but it was not advantageous generally in any biliary cases. 95 Although a recent retrospective study challenged this concept by showing that early ERCP was associated with lower mortality rates in a large, nationwide analysis of patients with biliary AP without cholangitis, 96 the findings of a well-designed, multicenter RCT support the initiative that ERCP in AP is indicated only in patients with cholangitis or persistent cholestasis. 97 The contradictions regarding the use of ERCP in AP lead to adjustments of study protocols, which resulted in identification of specific subpopulation of patients (ie, those with cholangitis), who can benefit the most from the intervention if it is performed in a timely manner.…”
Section: Future Possibilities Of Precision Medicine In Apmentioning
confidence: 99%
“… 97 The contradictions regarding the use of ERCP in AP lead to adjustments of study protocols, which resulted in identification of specific subpopulation of patients (ie, those with cholangitis), who can benefit the most from the intervention if it is performed in a timely manner. Since some results still question these recommendations, 96 further studies are warranted for fine-tuning the best target population, and, thereby, to further increase the efficacy of early ERCP in AP. The successful completion of such fine-tuning could serve as a pursuable model for establishing personalized (precision) treatment in AP.…”
Section: Future Possibilities Of Precision Medicine In Apmentioning
confidence: 99%